2013
DOI: 10.4236/health.2013.511238
|View full text |Cite
|
Sign up to set email alerts
|

Current state of active trachoma among elementary school students in the context of ambitious national growth plan: The case of Ethiopia

Abstract: Trachoma is a classical disease of poverty. It is still the second leading cause of blindness in Ethiopia. Cognizant of the poor living condition of its people, every effort of the current government of Ethiopia is geared towards eradication of extreme poverty. The main aim of this study was to assess the current status and correlates of active trachoma among elementary school students. A cross sectional school-based study was conducted in Dangla town administration in the month of March 2012. Multistage sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 9 publications
6
15
3
Order By: Relevance
“…Thatched grass house roof (AOR (95% CI), 4.402 (1.425-13.597) had association with active trachoma, which is in line with a study done in central Ethiopia [49] and poor economic status (AOR (95% CI), 3.804 (1.267-11.424) were increase the odds of active trachoma, which is supported by the study done in Gonder, Ethiopia [42]. These association are also consistent with a literature that trachoma is a disease of poverty, overcrowding, and poor hygiene [8,9,24,28,33,36,40,45,46,50].…”
Section: %)] This Prevalence Puts the District On 3 Years Of Mass supporting
confidence: 83%
See 1 more Smart Citation
“…Thatched grass house roof (AOR (95% CI), 4.402 (1.425-13.597) had association with active trachoma, which is in line with a study done in central Ethiopia [49] and poor economic status (AOR (95% CI), 3.804 (1.267-11.424) were increase the odds of active trachoma, which is supported by the study done in Gonder, Ethiopia [42]. These association are also consistent with a literature that trachoma is a disease of poverty, overcrowding, and poor hygiene [8,9,24,28,33,36,40,45,46,50].…”
Section: %)] This Prevalence Puts the District On 3 Years Of Mass supporting
confidence: 83%
“…The presence of human excreta near to home (AOR (95%CI), 5.089 (2.011-12.876) also increased the odds of active trachoma. This is supported by a study conducted in Dera district, Ethiopia [46]. This study also reported not using soap while washing face were increasing the odds of acquiring active trachoma (AOR (95%CI), 4.493 (1.788-11.290) and it is supported by the study conducted in Dessie city, Ethiopia, and Gonder, Ethiopia [42,47].…”
Section: %)] This Prevalence Puts the District On 3 Years Of Mass supporting
confidence: 53%
“…In contrast, the prevalence of trachoma in Gazegibela district is much higher than was found in similar studies from other parts of Ethiopia, such as in Baso Liben district, Gondar zuria district, Kersa district, Dangla district and Dera woreda where prevalences of active trachoma were 24.1, 23.8, 25.2, 12 and 15.6 % respectively [6, 8, 9, 16, 17]. This difference might be due to poorer infrastructure and low health service coverage in Gazegibela district, which is also an area that is repeatedly drought affected and one of the food insecure districts of the Amhara region.…”
Section: Discussionmentioning
confidence: 60%
“…Sample size was determinedby using double population proportion formula, at 95% confidence interval, 80% power of the study, and 1 to 2 ratio. The proportions were taken at 25.2% rural and 12% urban prevalence of active trachoma among children from one up to nine years of age which was conducted in Kersa district and Dangila town, respectively [ 12 , 13 ]. The sample size was calculated by STATCALC program of EPI INFO version 1.1.7.14.…”
Section: Methodsmentioning
confidence: 99%
“…One nationwide survey on blindness, low vision, and trachoma reported that the national prevalence of active trachoma (either TF or TI) among children with age group of 1–9 years is 40.14% [ 10 ]. More recent studies conducted in Dangila town of Amhara region and Kersa district of Oromia region showed the prevalence of active trachoma among children age 1–9 years were 12% and 25.2%, respectively [ 11 – 13 ].…”
Section: Introductionmentioning
confidence: 99%